Alternation of the gut microbiota in metabolically healthy obesity: An integrated multiomics analysis - Chen, Han; Tang, Nana; Ye, Qiang; Yu, Xin; Yang, Ruoyun; Cheng, Hong; Zhang, Guoxin; Zhou, Xiaoying (Frontiers in Cellular and Infection Microbiology, 2022)
Background Although the gut microbiota may be involved in obesity onset and progression, the exact association of the gut microbiota in metabolically healthy obesity (MHO) remains largely unknown. Methods An integrated paired-sample metagenomic analysis was conducted to investigate the gut microbial network and biomarkers of microbial species from the MHO and healthy non-obese subjects in the GMrepo database. Further explorations were performed in the MHO mice model using a multiomics analysis to detect changes in the composition and function of the intestinal microbiome and associated metabolites. Results In the human study, 314 matched metagenomic data were qualified for the final analysis. We identified seven significantly changed species possibly involved in MHO pathogenesis (MHO-enriched: Bacteroides vulgatus, Megamonas sp; MHO-depleted: Butyrivibrio crossotus, Faecalibacterium prausnitzii, Bacteroides cellulosilyticus; Eubacterium siraeum; Bacteroides massiliensis). In the murine study, we found 79 significantly-changed species which may have possible associations with the MHO phenotype. The depletion of Bacteroides cellulosilyticus was commonly recognized in the human and murine MHO phenotype. Consistent with the metagenomic data, liquid chromatography-mass spectrometry (LC/MS) revealed significantly changed gut metabolites, which may promote MHO pathogenesis by altering the amino acids and lipid metabolic pathways. In the microbe-metabolites interaction analysis, we identified certain fatty acids (Dodecanedioic acid, Arachidic Acid, Mevalonic acid, etc.) that were significantly correlated with the MHO-enriched or depleted species. Conclusion This study provides insights into identifying specific microbes and metabolites that may involve in the development of obesity without metabolic disorders. Future modalities for MHO intervention may be further validated by targeting these bacteria and metabolites.